Diaphragm Thickening Fraction as a Prognostic Imaging Marker for Postoperative Pulmonary Complications in Robot-Assisted Laparoscopic Prostatectomy Requiring the Trendelenburg Position and Pneumoperitoneum. (23rd June 2021) - Yu, Jihion; Lee, Yongsoo; Park, Jun-Young; Hwang, Jai-Hyun; Kim, Young-Kug
Abstract : Background . Robot-assisted laparoscopic prostatectomy (RALP) frequently entails postoperative pulmonary complications (PPCs) due to the Trendelenburg position and pneumoperitoneum. Diaphragm thickening fraction (TF) as an imaging marker can offer the advantage of predicting respiratory outcomes. Therefore, we evaluated the effect of diaphragm TF on the occurrence of PPCs in RALP. Methods . We measured the preoperative thickness of the diaphragm at peak inspiration (T pi ) and end expiration (T ee ) using ultrasonography. Diaphragm TF was calculated as TF = T pi – T ee / T ee . A receiver operating characteristic (ROC) curve analysis of TF was performed. After dividing patients into two groups according to the optimal TF cut-off value, we compared the occurrence of PPCs between the groups. The predictivity of diaphragm TF for the occurrence of PPCs was evaluated. Results . Of 145 patients, 40 patients (27.6%) developed PPCs. Patients with PPCs had a significantly lower TF than those without PPCs (0.31 ± 0.09 vs. 0.39 ± 0.11, P < 0.001 ). In the ROC curve analysis, the optimal TF cut-off value was 0.28. The patients were divided into TF ≥ 0.28 group (n = 114 ) and TF < 0.28 group (n = 31 ). The incidence of PPCs was significantly higher in the TF < 0.28 group than in the TF ≥ 0.28 group (51.6% vs. 21.1%, P = 0.001 ). Diaphragm TF < 0.28 was associated with a higher incidence of PPCs than diaphragm TF ≥ 0.28 (odds   ratio = 4.534, 95% confidence interval [1.763–11.658], P = 0.002 ). Conclusion . Preoperative diaphragm TF < 0.28 was associated with an increased incidence of PPCs, suggesting that diaphragm TF as a prognostic imaging marker provides useful information on PPCs in RALP requiring the Trendelenburg position and pneumoperitoneum. Trial Registry Number . This trial is registered with KCT0005028 .